2023
DOI: 10.31004/cendekia.v7i2.2211
|View full text |Cite
|
Sign up to set email alerts
|

Profil Literasi Matematis Peserta Didik Berdasarkan Level Kemampuan Pemecahan Masalah Soal PISA

Abstract: Pada saat ini, kemajuan dunia di bidang pendidikan sangat berkembang pesat, termasuk matematika. Hal tersebut menuntut seluruh peserta didik bukan hanya sekedar mahir berhitung, melainkan mampu mengaplikasikan segala konsep yang ada di matematika dalam kehidupan. Literasi matematika merupakan kemampun yang harus dimiliki peserta didik dalam menggunakan matematika untuk memecahkan masalah dalam berbagai konteks. Penelitian ini bertujuan untuk mendeskripsikan kemampuan literasi matematika berdasarkan level kemam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Understanding scientific concepts is crucial for students to comprehend various aspects of the environment, contemporary society, technology, health, and economics (Nuryanti et al, 2023). The ability of students to engage in mathematical literacy is equally important as it requires them to be proficient in formulating, applying, and interpreting various mathematical contexts in life (Nisa & Faradiba, 2023). In order to be successful in science and mathematics, students must first read and understand the text and symbols well, and interpret what they read.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Understanding scientific concepts is crucial for students to comprehend various aspects of the environment, contemporary society, technology, health, and economics (Nuryanti et al, 2023). The ability of students to engage in mathematical literacy is equally important as it requires them to be proficient in formulating, applying, and interpreting various mathematical contexts in life (Nisa & Faradiba, 2023). In order to be successful in science and mathematics, students must first read and understand the text and symbols well, and interpret what they read.…”
Section: Introductionmentioning
confidence: 99%
“…The mathematical literacy skills of junior high school students investigated by Khoirudin et al (2017) revealed that students are still in the level 1 category, indicating low mathematical abilities. Mathematical literacy was also examined by Nisa and Faradiba (2023), whose research findings indicated that students with low-level problemsolving abilities could not meet the indicators of mathematical literacy, while students with moderate-level problem-solving abilities did not fully complete the indicators of mathematical literacy.…”
Section: Introductionmentioning
confidence: 99%
“…Standar kompetensi dan keterampilan dasar matematika yang diuraikan dalam dokumen ini berfungsi sebagai landasan pembelajaran untuk mengembangkan keterampilan yang tercantum di atas (Fadhillah & Yulia, 2023;Wahyuningtyas et al, 2022). Hal ini juga bertujuan untuk mengembangkan kemampuan menggunakan matematika untuk memecahkan masalah dan mengkomunikasikan gagasan dan pemikiran dengan menggunakan simbol, tabel, diagram, dan media lainnya (Nanda Muliawati & Sutirna, 2022;F. Nisa & Faradiba, 2023;Umam et al, 2021).…”
unclassified